2019
DOI: 10.33510/statera.2019.1.1.34-46
|View full text |Cite
|
Sign up to set email alerts
|

Kondisi Keuangan, Opinion Shopping dan Opini Audit Going Concern pada Perusahaan Pertambangan yang Terdaftar di BEI

Abstract: Going concern audit opinion is the auditor's opinion to ascertain whether the company can maintain the survival of the entity. The importance of disclosing the company's survival will have an impact on steakholder valuation and trust. The purpose of this study was to determine the effect of financial conditions, opinion shopping and disclosure on going concern audit opinions on mining companies listed on the Indonesia Stock Exchange (IDX) during the period between 2014-2017.The population in this study are min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
2
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 7 publications
0
1
2
9
Order By: Relevance
“…The results of research by Fadli & Triyanto (2020) show that financial conditions have a negative effect on going-concern audit opinion, from these results it can be concluded that the higher the financial condition, the smaller the chance for the auditor to give a going-concern opinion, while the lower the financial condition, the more likely the auditor is to give an opinion going concern audits will be even greater. In contrast to the results of research conducted by Effendi (2019) who found that financial conditions did not affect going-concern audit opinions, this condition occurs when the auditor considers other factors such as economic conditions or company growth.…”
Section: Introductioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The results of research by Fadli & Triyanto (2020) show that financial conditions have a negative effect on going-concern audit opinion, from these results it can be concluded that the higher the financial condition, the smaller the chance for the auditor to give a going-concern opinion, while the lower the financial condition, the more likely the auditor is to give an opinion going concern audits will be even greater. In contrast to the results of research conducted by Effendi (2019) who found that financial conditions did not affect going-concern audit opinions, this condition occurs when the auditor considers other factors such as economic conditions or company growth.…”
Section: Introductioncontrasting
confidence: 83%
“…For companies that have good financial conditions, the auditor will not issue a going concern audit opinion. According to Effendi (2019), an auditor will usually consider financial conditions when giving a going concern audit opinion. Poor financial conditions will encourage auditors to tend to give a going concern audit opinion.…”
Section: Introductionmentioning
confidence: 99%
“…Hasil penelitian yang sama juga dikemukakan oleh Dewi & Latrini (2018) yang menyatakan bahwa financial distress memiliki efek terhadap opini audit going concern. Sebaliknya, menurut hasil penelitian yang pernah dilaksanakan oleh Effendi (2019) financial distress tidak berpengaruh terhadap opini audit going concern.…”
Section: Prasetyo Ramadhanunclassified
“…Dapat dijelaskan bahwa pergerakan apapun yang terjadi pada financial distress tidak akan berdampak pada opini audit going concern. Hasil penelitian ini selaras dengan milik Effendi (2019) namun berseberangan dengan hasil penelitian Nugroho et al, (2018) dan Dewi & Latrini (2018). Potensi kebangkrutan yang mungkin terjadi pada suatu perusahaan tidak memicu auditor membuat pertimbangan kepada laporan keuangan suatu entitas guna menerbitkan opini audit going concern.…”
Section: Pembahasanunclassified
See 1 more Smart Citation